Parasport medicine and its challenges: Between athletic competition and the disability rights movement - a narrative review - Zimniak, Maria Weronika; Jakubczak, Zofia; Głąbień, Marta; Miłkowski, Paweł; Kusiak, Karolina; Aleksandrowicz, Daria; Kuśnierz, Anna; Wieczorek, Olga; Kondratowicz, Aneta; Śliwiak, Patryk (Quality in Sport, 2024)
Introduction: The field of Paralympic medicine examines the healthcare issues that are specific to athletes with disabilities. This article presents a historical phenomenon in which the introduction of further activities for patients with neurological conditions led to the hosting of the Paralympic Games. The article describes the complexity of inclusivity in disability health research and outlines the historical context of the emergence of this field of sports medicine. It also presents the main challenges posed by the developing parasport. One of the most significant issues is to guarantee that competition is conducted with the greatest degree of equity possible. This entails ensuring the precision of classification, preventing the over-medicalisation of athletes. It is also imperative that athletes with special requirements are provided with the appropriate support and equipment. The creation of adequate care pathways requires a challenging process, largely due to the inconclusive nature of research findings over the years. Further investigation is necessary to gain a more nuanced understanding of this relatively new area of study. Purpose of work: The aim of this article is to provide an overview of the broader challenges that paramedicine is facing in relation to the rapid development of this branch of sports medicine. Materials and methods: This article is based on the literature found in Pubmed database and other scientific databases. References were researched using following keywords: paralympic games, persons with disabilities, paramedicine, para-athletes, Conclusions: The advancement of Paralympic medicine is markedly expedited by a synthesis of qualitative and quantitative research methodologies. The integration of these two approaches yields invaluable insights into the personal perspectives of athletes on their health, while also facilitating statistically significant, evidence-based results on the analysis of large groups of athletes.